The Coastal Morphology and Sedimentology of Cape Hatt Peninsula - Sempels, J.-M. (ARCTIC, 1987)
A small peninsula located on northern Baffin Island was selected as the site for an experimental oil spill. The experiment required three similar bays, one to serve as control and two to compare the fate and behaviour of oil and an oil-dispersant mix spilled in the nearshore zone. Geomorphic and sedimentologic observation indicate that (1) the shoreline sediments of Cape Hatt are reworked glacial deposits, (2) bays facing Eclipse Sound are the most exposed to wave and ice action and those of Z-Lagoon are the most sheltered, (3) there is a westerly sediment transport direction in the bays of Eclipse Sound, a winnowing of fines from the most exposed bays of Z-Lagoon and several transport directions in Ragged Channel and (4) ice action is the most important process at Cape Hatt. Qualitative assessment of these features was used to recommend that Bay 10 be used for control, Bay 9 for the oil-alone experiment and Bay 11 for the oil-dispersant mix experiment. Geological features, however, reflect the integration of all processes operating at Cape Hatt over long periods of time and do not warrant as high a priority as meteorological and oceanographic criteria in the final selection of bays for the BIOS Project.Key words: Eastern Arctic, Cape Hatt, shoreline morphology, sedimentology Mots clés: Arctique de l’est, cap Hatt, morphologie des côtes, sédimentologie